Social relations and power - Labourdette, Sergio (2007)
This paper presents an explanatory typology of social relations which moves forward from those habitual and known by social disciplines, and labels the three types: actions-strategies-institutions. We set out to research characteristics, specificities, relevance of and differences between each type, as well as their interactions and interweaving, which make up the complexity of social relations. Moreover, mutual interdependence between the said social categories is established, which corresponds to a new conceptualization of power . This avoids traditional reductionism and rescues rarely taken-into-account capacities and determinations. The pair "social relations and power" makes up a necessary and indispensable framework to tackle the various problems of the social world.